Diversidad del orden Lepidoptera (Hesperioidea y Papilionoidea) de la ciudad Corrientes, Argentina - Gabriela Lazzeri, María; Esther Bar, María; Pieri Damborsky, Miryam (Revista de Biología Tropical, 2011)
Urbanization is one of the most important threats for biodiversity. Among many different organisms, butterflies are useful indicators of environment diversity and quality. The aim of this study was to investigate the Lepidoptera from Corrientes city. Random samplings were performed at two sites: a native forest situated in Santa Catalina district and an urban area, Parque Mitre. The captures were carried out using entomological nets, at four seasons between January to October 2007. A total of 1 114 butterflies, represented by six families: Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, Pieridae and Riodinidae and 18 subfamilies were record-ed. Fifty-nine genera and 75 species were identified; Anartia jatrophae jatrophae was the mostabundant species at both localities. This species and Urbanus procne, Phoebis sennae marcellina, Pyrgus orcus and Dryas iuliaalcionea were, among other seven, captured at all months. Highest values of abundance were registered during the warmest seasons. Santa Catalina presented the largest abundance (n=701), richness (S=74) and diversity (H’=3.87). A total of 413 individuals and 52 species were identified at Parque Mitre, and Shannon diversity index was 3.58. The obtained data reveals a high species richness and similarity at both sites.